2022
DOI: 10.3389/fnut.2022.974694
|View full text |Cite
|
Sign up to set email alerts
|

Different oral and gut microbial profiles in those with Alzheimer's disease consuming anti-inflammatory diets

Abstract: The number of people living with Alzheimer's disease (AD) is increasing alongside with aging of the population. Systemic chronic inflammation and microbial imbalance may play an important role in the pathogenesis of AD. Inflammatory diets regulate both the host microbiomes and inflammatory status. This study aimed to explore the impact of inflammatory diets on oral-gut microbes in patients with AD and the relationship between microbes and markers of systemic inflammation. The dietary inflammatory properties an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 107 publications
1
1
0
Order By: Relevance
“…Relative abundance analysis revealed the downward trends in phyla Proteobacteria , Actinobacteria , and Bacteroidota in the AD group. At the same time, Firmicutes was significantly more abundant in AD patients, which aligns with the results of Chen et al [ 41 , 42 ]. The results on the lower abundance of s_Haemophilus_parainfluenzae , s_Prevotella_melaninogenica , s_Prevotella_histicola , and s__Actinomyces_oris in AD patients are partly consistent with Liu et al data [ 12 ].…”
Section: Discussionsupporting
confidence: 91%
“…Relative abundance analysis revealed the downward trends in phyla Proteobacteria , Actinobacteria , and Bacteroidota in the AD group. At the same time, Firmicutes was significantly more abundant in AD patients, which aligns with the results of Chen et al [ 41 , 42 ]. The results on the lower abundance of s_Haemophilus_parainfluenzae , s_Prevotella_melaninogenica , s_Prevotella_histicola , and s__Actinomyces_oris in AD patients are partly consistent with Liu et al data [ 12 ].…”
Section: Discussionsupporting
confidence: 91%
“…There are several studies investigating a possible connection between the oral microbiome community structure and AD. Through a MEDLINE search (search terms: 'oral microbiota', 'oral microbiome' and 'alzheimer', 'dementia', 'cognitive', 'cognition'), we identified 13 studies investigating the connections between AD and the oral microbiome (Cockburn et al, 2012;Bathini et al, 2020;Holmer et al, 2021;Wu et al, 2021;Yang et al, 2021;Chen et al, 2022a;Chen et al, 2022b;Chen et al, 2022c;Cirstea et al, 2022;Fu et al, 2022;Taati Moghadam et al, 2022;Tadjoedin et al, 2022). For Chen et al 2022a andCirstea et al, 2022, full-text manuscripts could not be obtained.…”
Section: Oral Dysbiotic Signatures Are Associated With the Developmen...mentioning
confidence: 99%
“…Five studies (Cockburn et al, 2012;Bathini et al, 2020;Holmer et al, 2021;Yang et al, 2021;Chen et al, 2022c) additionally included a third group of MCI patients, or people with subjective cognitive decline, or further differentiated into mild and moderate AD (Chen et al, 2022c). Chen et al (b) had no healthy control group, but divided their AD patients into three groups regarding the patients' nutritional habits (Chen et al, 2022b), based on the so-called 'dietary inflammatory index' (DII) (Phillips et al, 2019). One study employed a longitudinal design without a control group, but with a comparison of the oral microbiota before and after a 24-week oral health intervention (Chen et al, 2022a).…”
Section: Oral Dysbiotic Signatures Are Associated With the Developmen...mentioning
confidence: 99%
See 1 more Smart Citation
“…The flexible vegetarian diet that emphasizes increased vegetable consumption and reduced meat intake, is very effective in weight loss 13 . Anti-inflammatory diets focusing on fish, fruits, and vegetables have also been demonstrated a suppressive effect on the risk of Alzheimer's disease, Parkinson's disease, atherosclerosis, heart disease, and muscle wasting 14 17 . Furthermore, a meta-analysis showed that the addition of the antioxidant vitamin E to the treatment of depression and anxiety might be beneficial 18 .…”
Section: Introductionmentioning
confidence: 99%